Hybrid assembly using long reads resolves repeats and completes the genome sequence of a laboratory strain of Staphylococcus aureus subsp. aureus RN4220. Issue 11 (November 2022) - Panthee, Suresh; Hamamoto, Hiroshi; Paudel, Atmika; Kaito, Chikara; Suzuki, Yutaka; Sekimizu, Kazuhisa
Abstract: Staphylococcus aureus RN4220 has been extensively used by staphylococcal researchers as an intermediate strain for genetic manipulation due to its ability to accept foreign DNA. Despite its wide use in laboratories, its complete genome is not available. In this study, we used a hybrid genome assembly approach using minION long reads and Illumina short reads to sequence the complete genome of S. aureus RN4220. The comparative analysis of the annotated complete genome showed the presence of 39 genes fragmented in the previous assembly, many of which were located near the repeat regions. Using RNA-Seq reads, we showed that a higher number of reads could be mapped to the complete genome than the draft genome and the gene expression profile obtained using the complete genome also differs from that obtained from the draft genome. Furthermore, by comparative transcriptomic analysis, we showed the correlation between expression levels of staphyloxanthin biosynthetic genes and the production of yellow pigment. This study highlighted the importance of long reads in completing microbial genomes, especially those possessing repetitive elements. Highlights: S. aureus RN4220 is used as an intermediate strain for genetic manipulation. We completed its genome and found 39 fragmented genes in previous genome assembly. RNA-Seq analysis improved mapping of the reads with the use of complete genome. Expression of staphyloxanthin biosynthetic genes was correlated with its production. Abstract : Staphylococcus aureus ; RN4220; Complete genome; Hybrid assembly; RNA-Seq; Repeat regions; Staphyloxanthin.